Videofluoroscopy Instrument to Identify the Tibiofemoral Contact Point Migration for Anterior Cruciate Ligament Reconstruction Follow-up: CINARTRO. (April 2016) - Simini, F; Santos, D; Francescoli, L
Abstract: We measure the Tibiofemoral contact point migration to offer clinicians a tool to evaluate Anterior Cruciate Ligament reconstruction. The design of the tool includes a C arm with fluoroscopy, image acquisition and processing system, interactive software and report generation for the clinical record. The procedure samples 30 images from the videofluoroscopy describing 2 seconds movements of hanging-to-full-extension of the knee articulation. A geometrical routine implemented in the original equipment (CINARTRO) helps capture tibial plateau and femoral condile profile by interaction with the user. The tightness or looseness of the knee is expressed by the migration given in terms of movement of the femur along the tibial plateau, as a percentage. We automatically create clinical reports in standard Clinical Document Architecture or CDA format. A special phantom was developed to correct the "pin cushion effect" in Rx images. Five cases of broken ACL patients were measured giving meaningful results for clinical follow up. Tibiofemoral contact point migration was measured as 60% of the tibial plateau, with standard deviation of 6% for healthy knees, 4% when injured and 1% after reconstruction.